Impact of Coracohumeral Ligament Release on Treatment Outcomes in Patients with Idiopathic Adhesive Capsulitis - Strafun, S.S.; Bohdan, S.V.; Yuriichuk, L.M.; Serhiienko, R.O. (TERRA ORTHOPAEDICA, 2024)
Background. The coracohumeral ligament restricts external rotation of the shoulder joint and, along with the upper, middle, and lower glenohumeral ligaments, participates in stabilizing the shoulder joint. There is ongoing debate regarding the division of this anatomical structure in patients with limited external rotation. Objective: to compare the treatment outcomes of patients with idiopathic adhesive capsulitis who underwent coracohumeral ligament release along with selective capsulotomy to those who underwent only partial coracohumeral ligament release. Material and Methods. We treated 85 patients with idiopathic adhesive capsulitis, who were divided into two groups: group 1 underwent selective anterior capsulotomy of the shoulder joint with the division of the middle and lower glenohumeral ligaments, biceps long head tenotomy, subacromial decompression, and partial coracohumeral ligament release; group 2 underwent a similar surgical procedure with complete coracohumeral ligament excision. The average age of the patients was 47.9±19.1 years. The function of the shoulder joint was assessed using the Constant Shoulder Score and VAS scales before surgery and at 3 and 6 months postoperatively. Results. At 3 months postoperatively, group 2 showed a slightly better functional outcome according to the Constant Shoulder Score (12.2±6.9 points) compared to group 1 (18.1±6.4 points, p=0.038). At 6 months postoperatively, group 1 had a mean Constant Shoulder Score of 15.1±7 points, while group 2 had a score of 10.1±6.3 points (p=0.02). Conclusions. Excision of the coracohumeral ligament in patients with idiopathic adhesive capsulitis allows for better functional outcomes according to the Constant Shoulder Score and VAS at both 3 and 6 months postoperatively.